Pharmacist Disciplinary Action: What Do Pharmacists Get in Trouble for? - Ai-Leng Foong-Reichert, Kelly A. Grindrod, David J. Edwards, Zubin Austin and Sherilyn K.D. Houle (Healthcare Policy, 2023)
Objective: This study aims to determine the reasons for disciplinary action and resultant consequences for Canadian pharmacists and any associations with demographic factors. Methods: Regulatory body disciplinary action cases from 10 Canadian provinces were coded. Demographic information was coded. Results: There were 665 pharmacist cases from nine provinces between January 2010 and December 2020. The rate of disciplinary action was low (1.37 cases/1,000 practitioners/year). Professional misconduct was the most common category of violation. Male pharmacists were overrepresented in disciplinary action cases. Most cases involved community pharmacists. Conclusion: This study is the first, to our knowledge, in Canada to analyze the demographic factors of pharmacists subjected to disciplinary action. It updates a previous review of pharmacist disciplinary action (Foong et al. 2018).
Keywords: disciplinary action, clinical incompetence, governance, professional misconduct, primary care, pharmacy, pharmacist